Gaya Kepemimpinan dan Motivasi Kerja terhadap Komitmen Kerja Karyawan Bank Nagari, Cabang Pasar Raya, Padang - Hilma Suyana (Majalah Sainstekes, 2020)
The purpose of this study was to analyze the effect of leadership style and work motivation toward employee commitment Nagari Bank, Pasar Raya Branch, Padang. This type of research was to study on causality. The population in this study was within the Nagari Bank, Pasar Raya Branch, Padang, amounting to 226 employees. The sample size was 144 employees. The technique of data analysis was descriptive analysis, test analysis and hypothesis testing requirements with path analysis. The study found that the leadership style and work motivation significantly affected the organizational commitment of employees of the Nagari Bank, Pasar Raya Branch, Padang.